Tree crown overlap improves predictions of the functional neighbourhood effects on tree survival and growth. (17th October 2018) - Zambrano, Jenny; Fagan, William F.; Worthy, Samantha J.; Thompson, Jill; Uriarte, Maria; Zimmerman, Jess K.; Umaña, Maria N.; Swenson, Nathan G.
Abstract: Investigations of forest community structure and dynamics have been facilitated by the use of neighbourhood models that examine the interactions between a focal tree and its neighbours using a fixed radius. However, different studies have chosen different radii without clear reasons, hampering the understanding of mechanisms structuring tree communities. Using functional trait and tree demography data from the Luquillo subtropical forest in Puerto Rico, we compared fixed‐neighbourhood models with a canopy overlap model, in which tree crown overlap is used as an indicator of neighbourhood crowding. Analyses that combine functional trait and demographic data provide a mechanistic understanding of observed patterns of community structure and dynamics as they provide insights into the linkages between phenotypes and the environment. Overall, canopy overlap models had better support when compared to neighbourhood models using a fixed radius, suggesting that the fixed radius approach does not capture the full extent of competitive interactions among trees. Moreover, the effects of functional neighbourhood on tree survival and growth differ depending on the type of approach used and lead to different conclusions with respect to the drivers of tree community dynamics. Synthesis . In summary, our findings highlight the utility of neighbourhood models based on tree crown overlap, and suggest that applying this same approach to different plots and forests will facilitate comparisons across systems and improve our understanding of the mechanisms that drive the structure and dynamics of tree communities. Abstract : Our findings highlight the utility of neighbourhood models based on tree crown overlap, and suggest that applying this same approach to different plots and forests will facilitate comparisons across systems and improve our understanding of the mechanisms that drive the structure and dynamics of tree communities.